Shared inclusive reading project: a different way of reading - Mangas, Catarina (2020)
The communication intends to present the PLIP – Projeto de Leitura Inclusiva Partilhada, which is a shared inclusive reading project, started in 2013, in the Inclusion & Accessibility in Action Research Center (iACT). This project adapts books in alternative formats such as: braille text; big print; raised/high contrast pictures; audiobook; video book with sign language; pictographic; etc. The multiform at kits are free and available online in digital format, so that everyone can print them (with normal or special equipment – eg. braille printer or relief) or used them directly on computers, tablets or smartphones (through screen readers). The adaptation of original books or books that have been already published in the traditional format, allows more people to have access to literary works, such as the elderly, readers with disabilities, pre-school children, among others. In addition to the development of multiform at kits, the project aims to promote training sessions for those who want to learn how to adapt books and it also supports reading actions that can make adapted stories available for everyone. All inputs are welcome in this dynamic, open and shared project. PLIP is developed in the community, creating links between generations, places, and different areas of knowledge and living. It is considered a network of good practices, giving great visibility to the independent work that has been successfully developed in many different contexts.